Analisis Unsur Intrinsik Novel “Di Balik Tangga Bukit Langit” Karya Ratna Pande - Melsa Nuraisyah; Selfi Novita Mariam (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Literature reflects life and describes human social, cultural, and emotional realities. Through literature, readers understand various aspects of life (Simaremare, 2023). This study uses descriptive qualitative methods to analyze the novel Behind the stairs of Bukit Langit, focusing on themes, characters, plot, and moral messages. The main theme is friendship and love, with an emotional conflict between love and loyalty. The main character, Oryza, faces dilemmas of love and friendship, which are finally resolved with honesty and understanding. The Novel conveys a message about the importance of honesty and overcoming difficult choices.